ORIGAMI BANGAU DALAM SENI LUKIS SUREALIS - JEMMI HANDRA PRATAMA, Dra. Jupriani, M.Sn., Yasrul Sami, S.Sn., M.Sn. (Serupa The Journal of Art Education, 2018)
The purpose of the creation of the final work is to visualize the origami stork. Methods in this activity include preparation, elaboration, synthesis, concept realization, completion stage until displayed in exhibition activities. The style carried in this creation process is surrealism. This work provides the basic knowledge to the community about origami art which is a form of interest in origami stork, illustrated through 10 (ten) titles of work in surreal style: Life Frame, Freedom, Senbazuru (1000 origami stork), Sadako sasaki, Cage of freedom, Transformation freedom, Friendship with him, Still about loyalty, Endangered, Dancing on the clouds.Keywords: Origami Stork, Painting, Surrealism